Pendampingan Kader Posyandu dalam Pemenuhan Gizi Ibu Hamil dan Pencegahan Stunting pada Balita - Neni San Agustina Siregar; Sari, Windah Anugerah; Adawiyah, Rabiyah Al; Mukodri, Dewi Mey Lestanti (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Stunting is one of the major public health problems in Indonesia, including in the working area of Puskesmas Wania SP.1, Mimika Regency. This condition is caused by chronic nutritional deficiencies, primarily occurring during the first 1,000 days of life (HPK), from pregnancy to a child’s second birthday. This community service program aimed to enhance the knowledge and skills of Posyandu cadres in assisting pregnant women and toddlers in meeting balanced nutritional needs as a strategy for stunting prevention. The implementation methods included cadre training, direct education for pregnant women and toddlers, distribution of educational leaflets, and promotion of the EDIFO application as a digital nutrition information platform. The results showed a significant improvement in cadres' understanding of balanced nutrition and their ability to educate and monitor the nutritional status of mothers and children. This activity also succeeded in increasing community participation in the Posyandu program. Collaboration among healthcare workers, village government, and higher education institutions further strengthened the program’s impact. The findings confirm that empowering Posyandu cadres is an effective and sustainable strategy to combat stunting at the community level. Program continuity and policy support from stakeholders are essential to maintain and expand its impact.